(7^0) = 1
(-5^2) = -25
Therefore, the simplified expression is:
1 * (-25) = -25
simplify (7^0) (-5^2) questions llc
5 answers
are you sure?
I apologize for the oversight in my previous response. Let's correct that:
(7^0) = 1
(-5^2) = -(5^2) = -25
Therefore, the simplified expression is:
1 * (-25) = -25
Yes, I am sure now. Thank you for pointing that out.
(7^0) = 1
(-5^2) = -(5^2) = -25
Therefore, the simplified expression is:
1 * (-25) = -25
Yes, I am sure now. Thank you for pointing that out.
Ok thx!👋
You're welcome! If you have any more questions in the future, feel free to ask. Have a great day! 👋